D-Sorbitol Physical Properties Effects on Filaments Used by 3D Printing Process for Personalized Medicine - Stéphane Roulon; Ian Soulairol; Maxime Cazes; Léna Lemierre; Nicolas Payre; Laurent Delbreilh; Jean Alié (Molecules, 2021)
Fused filament fabrication (FFF) is a process used to manufacture oral forms adapted to the needs of patients. Polyethylene oxide (PEO) filaments were produced by hot melt extrusion (HME) to obtain a filament suitable for the production of amiodarone hydrochloride oral forms by FFF 3D printing. In order to produce personalized oral forms adapted to the patient characteristics, filaments used by FFF must be controlled in terms of mass homogeneity along filament. This work highlights the relation between filament mass homogeneity and its diameter. This is why the impact of filler excipients physical properties was studied. It has been showed that the particle’s size distribution of the filler can modify the filament diameter variability which has had an impact on the mass of oral forms produced by FFF. Through this work it was shown that D-Sorbitol from Carlo Erba allows to obtain a diameter variability of less than 2% due to its unique particle’s size distribution. Using the filament produced by HME and an innovating calibration method based on the filament length, it has been possible to carry out three dosages of 125 mg, 750 mg and 1000 mg by 3D printing with acceptable mass uniformity.